Experimental fatigue evaluation of underwater steel panels retrofitted with fiber reinforced polymers - Hudak, Lauren, author; Mahmoud, Hussam, advisor; Riveros, Guillermo, committee member; Atadero, Rebecca, committee member; Arneson, Erin, committee member (Colorado State University. Libraries, 2019)
Many steel structures are susceptible to fatigue loading and damage that can potentially threaten their integrity if not monitored and repaired. Steel hydraulic structures (SHS), in particular, experience fatigue loading during operation and are exposed to harsh environmental conditions that can further reduce fatigue life through mechanisms such as stress corrosion cracking and corrosion fatigue. Dewatering to complete inspections or repairs to SHS is time consuming and leads to economic losses, and current repair methods, such as rewelding, often cause new cracks to form after relatively few cycles, requiring repeated inspection and repair. The use of bonded carbon fiber reinforced polymer (CFRP) to repair fatigue cracks in metallic structures has been successfully demonstrated in other industries, and recent work has suggested that the method can also offers a more reliable repair method for SHS. The very few studies regarding CFRP retrofits of SHS indicate that early bond failure often controls the degree of fatigue life extension provided by the repair. This study aims to extend previous experimental studies and further increase the fatigue life of repaired steel components by employing methods to improve CFRP bonding. Additionally, the use of basalt reinforced polymer (BFRP) as an alternative to CFRP is proposed. Limited examples of BFRP used in structural applications are available, but BFRP is attractive for SHS because it does not react galvanically with steel as CFRP does. In this study, four large-scale center-cracked panels were tested under constant amplitude fatigue loading. Of the four specimens, one was retrofitted with CFRP, and one was retrofitted with BFRP. To achieve an environment similar to that experienced by SHS, the two retrofitted specimens and one unretrofitted specimen were submerged in fresh water during testing. Remaining fatigue life was used as the primary metric for assessing the efficacy of the retrofit method. Results indicated that the use of both CFRP and BFRP are effective at extending fatigue life. The extent of fatigue life extension was still controlled by the quality of the FRP bond to steel; however, bond behavior was improved in comparison to previous underwater applications.